Answer:
bbbbbbbbbnbbbb bbbbbbbbbb
Answer:
x=8°
y=29°
Step-by-step explanation:
vertically opposite angles are equal
so 5x+9°=y+20°
therefore 5x-y=11°
Alternate angles are equal
so 4x+17°=y+20°
therefore 4x-y=3°
equation 1....... 5x-y=11°
equation 2......4x-y=3°
using elimination method x=8°
y=29°
Answer: 9cm
Step-by-step explanation:
![7x10=70cmx^{2}](https://tex.z-dn.net/?f=7x10%3D70cmx%5E%7B2%7D)
4(x)=4x
1.) 70+4x=106 (subtract 70 on both sides)
2.)4x=36 (divide 4 on both sides)
3.)x=9
Answer:
The second term of the sequence is 8 False ⇒ B
The third term of the sequence is 3 True ⇒ A
The fourth term of the sequence is -3 True ⇒ A
Step-by-step explanation:
The form of the recursive rule is:
f(1) = first term; f(n) = f(n - 1) + d, where
- f(n - 1) is the term before the nth term
- d is the common difference
∵ f(1) = 15, f(n) = f(n - 1) - 6 for n ≥ 2
∴ The first term = 15
∴ d = -6
let us find the 2nd, 3rd, and 4th terms
∵ n = 2
∴ f(2) = f(1) - 6
∵ f(1) = 15
∴ f(2) = 15 - 6 = 9
∴ The second term is 9
∴ The second term of the sequence is 8 False
∵ n = 3
∴ f(3) = f(2) - 6
∵ f(2) = 9
∴ f(3) = 9 - 6 = 3
∴ The third term is 3
∴ The third term of the sequence is 3 True
∵ n = 4
∴ f(4) = f(3) - 6
∵ f(3) = 3
∴ f(4) = 3 - 6 = -3
∴ The fourth term is -3
∴ The fourth term of the sequence is -3 True
Answer:
Correct answer: (a - 4) · (a + 6)
Step-by-step explanation:
Given:
a² - 4a - 24 + 6a = a² - 4a + 6a - 24 = a (a - 4) + 6 (a - 4) = (a - 4) · (a + 6)
God is with you!!!